A report on physical performance in female patients diseased for idiopathic scoliosis - Laurentowska, Maria; Szczepanowska, Ewa; Głowacki, Maciej; Rychlewski, Tadeusz (Anthropological Review, 2001)
The purpose of this study was to examine physical performance and exercise tolerance in patients with scoliosis in comparison with healthy girls of the similar age. Results of the study show the similar aerobic performance in both groups. However, exercise tolerance was significantly lower in patients with scoliosis than in the control group. Similarly, resting values of cardiac output and stroke volume were significantly lower in girls with scoliosis as compared with healthy girls.